Bugis Folk Songs as a Source of Linguistic Learning Based on Local Wisdom - Muhsyanur, Muhsyanur; Weifen, Qin; Murugesan, Manivannan (Fakultas Ilmu Budaya, Universitas Jambi, 2026)
This research aims to examine Bugis folk songs (elong) as a source of linguistic learning grounded in authentic, contextual local wisdom. Bugis folk songs contain a wealth of phonological, morphological, syntactic, semantic, and pragmatic structures that have not been optimally utilized in formal education. Using an ethnolinguistic approach and qualitative content analysis, this study identifies five main elong genres and their relevant linguistic features for learning. The results of the study show that Bugis folk songs contain complex layers of meaning, diverse language registers, and socio-cultural values that can enrich students' holistic understanding of the structure and function of language. The integration of elong into the linguistic curriculum not only enhances linguistic competence but also strengthens cultural identity and preserves the intangible heritage of the Bugis. This study recommends the development of structured, context-based teaching modules as an innovation in regional linguistic learning. Abstrak Penelitian ini bertujuan untuk mengkaji lagu-lagu rakyat Bugis (elong) sebagai sumber pembelajaran linguistik berdasarkan kearifan lokal yang otentik dan kontekstual. Lagu-lagu rakyat Bugis mengandung banyak struktur fonologis, morfologis, sintaksis, semantik, dan pragmatis yang belum dimanfaatkan secara optimal dalam pendidikan formal. Dengan menggunakan pendekatan etnolinguistik dan analisis konten kualitatif, penelitian ini mengidentifikasi lima genre elong utama dan fitur linguistiknya yang relevan dengan pembelajaran. Hasil penelitian menunjukkan bahwa lagu rakyat Bugis mengandung lapisan makna yang kompleks, register bahasa yang beragam, dan nilai-nilai sosial budaya yang dapat memperkaya pemahaman holistik siswa tentang struktur dan fungsi bahasa. Integrasi elong ke dalam kurikulum linguistik tidak hanya meningkatkan kompetensi linguistik tetapi juga memperkuat identitas budaya dan melestarikan warisan takbenda Bugis. Penelitian ini merekomendasikan pengembangan modul pengajaran berbasis konteks yang disusun sebagai inovasi dalam pembelajaran linguistik daerah.